PEMANFAATAN AMPO SEBAGAI NUTRISI ALTERNATIF BAGI IBU HAMIL DI JATIWANGI, MAJALENGKA - Rahmat Nurdien Maulana; Rika Rahmawati; Nurul Khoiriyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Ampo is a natural mineral that is believed by some people in the Jatiwangi area to have good benefits for pregnant women. The practice of consuming ampo is known as geophagy. In ancient and modern human societies, geophagy has become a widely practiced and sometimes very complex practice that was first mentioned by Aristotle, described by Dioscorides in 40 A.C., as a means of making drugs and poisons (Danford, 1982). During the pregnancy phase more nutrients are needed to meet the intake for the mother and fetus. The eastern Majalengka region has a customary culture system, where pregnant women consume ampo. It is inseparable from the content contained in ampo seen from the needs of the mother and fetus during pregnancy. The purpose of this paper is to describe the benefits and effects of ampo consumption for pregnant women. The research data needed in the form of local wisdom of pregnant women in the Jatiwangi community who consume ampo obtained by using ethnographic methods. The results of several previous research publications were explored as knowledge that ampo has some nutrients such as calcium, iron, potassium, and zinc minerals that can be absorbed by the body. So that the use of ampo as an alternative nutrient for pregnant women is considered as local wisdom can be developed more broadly. Keywords: ampo, socialization, local wisdom, pregnancy.